Enhancement of the adaptive signature design for learning and confirming in a single pivotal trial. (5th May 2017) - Mi, Gu
Abstract : Because of the complexity of cancer biology, often the target pathway is not well understood at the time that phase III trials are initiated. A 2‐stage trial design was previously proposed for identifying a subgroup of interest in a learn stage, on the basis of 1 or more baseline biomarkers, and then subsequently confirming it in a confirmation stage. In this article, we discuss some practical aspects of this type of design and describe an enhancement to this approach that can be built into the study randomization to increase the robustness of the evaluation. Furthermore, we show via simulation studies how the proportion of patients allocated to the learn stage versus the confirm stage impacts the power and provide recommendations.